2010
DOI: 10.1590/s1516-05722010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da atividade antimicrobiana do extrato etanólico bruto da casca da sucupira branca (Pterodon emarginatus Vogel) - Fabaceae

Abstract: RESUMO:Pterodon emarginatus Vogel (Fabaceae) é uma árvore do Cerrado conhecida popularmente como "sucupira branca, faveiro, fava de sucupira e sucupira lisa" e utilizada na medicina popular em preparações anti-reumáticas, antiinflamatórias, analgésicas e antiinfecciosas. Esse trabalho teve por objetivo fazer a triagem fitoquímica do pó e avaliar a atividade antimicrobiana do extrato etanólico bruto das cascas da P. emarginatus contra bactérias Palavras-chave: plantas medicinais, CIM, bactériaABSTRACT: Evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 7 publications
0
8
0
8
Order By: Relevance
“…The improvement of the purification and isolation methods using mass and ultraviolet spectrometry and infrared and nuclear magnetic resonance techniques has allowed the elucidation of complex structures in plant materials [ 26 , 27 ]. Phytochemical studies on the genus Pterodon have demonstrated the presence of isoflavones, sesquiterpenes, and diterpenes in its fruit oil [ 1 , 28 – 30 ]; isoflavones and triterpenes in the wood [ 31 , 32 ]; alkaloids, saponins, glycosides, and steroids in the bark of the trees [ 24 , 33 ]; and steroids, sesquiterpenes, isoflavones, and saponins in the leaves [ 34 , 35 ].…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of the purification and isolation methods using mass and ultraviolet spectrometry and infrared and nuclear magnetic resonance techniques has allowed the elucidation of complex structures in plant materials [ 26 , 27 ]. Phytochemical studies on the genus Pterodon have demonstrated the presence of isoflavones, sesquiterpenes, and diterpenes in its fruit oil [ 1 , 28 – 30 ]; isoflavones and triterpenes in the wood [ 31 , 32 ]; alkaloids, saponins, glycosides, and steroids in the bark of the trees [ 24 , 33 ]; and steroids, sesquiterpenes, isoflavones, and saponins in the leaves [ 34 , 35 ].…”
Section: Phytochemistrymentioning
confidence: 99%
“…emarginatus bark showed a different outcome since the use of its ethanol extract against Gram-positive and Gram-negative bacteria and against the fungus Candida albicans was effective against Rhodococcus equi , Micrococcus luteus , Micrococcus roseus (MIC: 0.18 mg/mL), Serratia marcescens , Pseudomonas aeruginosa (MIC: 0.37 mg/mL), Enterobacter cloacae , and C . albicans (MIC: 0.74 mg/mL) [ 33 ].…”
Section: Traditional Use and Biological Activitiesmentioning
confidence: 99%
“…The seed oil and extracts of the bark and stems of P. emarginatus are used in Brazilian folk medicine to treat rheumatism, control diabetes, antimicrobial, anti-inflammatory and analgesic agent [7]. Among others, lupeol, botulin triterpenes, flavonoids, saponosides were identified in stem bark and seed extracts [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…The seeds of P. emarginatus have also been reported to have antimicrobial, anti‐ulcerogenic and leishmanicidal action (Dutra, Braga, Coimbra, Silva, & Barbosa, ). Tea made from the husk of the stalk is used to treat gynaecological infections (Alves et al., ; Bustamante et al., ; Leite de Almeida & Gottlieb, ; Lorenzi, ; Mors, Santos, Monteiro, & Gilbert, ; Santos et al., ). Oil from P. emarginatus has been used as an anti‐inflammatory agent, especially in the form of a microemulsion (Pascoa, Diniz, Florentino, Costa, & Bara, ) and as a nanoemulsion for biological control over the larvae of Aedes aegypti (Oliveira et al., ).…”
Section: Introductionmentioning
confidence: 99%